Phylogenetic Relationships Within the Hyper-Diverse Genus Eugenia (Myrtaceae: Myrteae) Based on Target Enrichment Sequencing - Giaretta, Augusto; Murphy, Bruce; Maurin, Olivier; Mazine, Fiorella F.; Sano, Paulo; Lucas, Eve (Frontiers in Plant Science, 2022)
Eugenia is one of the most taxonomically challenging lineages of flowering plants, in which morphological delimitation has changed over the last few years resulting from recent phylogenetic study based on molecular data. Efforts, until now, have been limited to Sanger sequencing of mostly plastid markers. These phylogenetic studies indicate 11 clades formalized as infrageneric groups. However, relationships among these clades are poorly supported at key nodes and inconsistent between studies, particularly along the backbone and within Eugenia sect. Umbellatae encompasses ca. 700 species. To resolve and better understand systematic discordance, 54 Eugenia taxa were subjected to phylogenomic Hyb-Seq using 353 low-copy nuclear genes. Twenty species trees based on coding and non-coding loci of nuclear and plastid datasets were recovered using coalescent and concatenated approaches. Concordant and conflicting topologies were assessed by comparing tree landscapes, topology tests, and gene and site concordance factors. The topologies are similar except between nuclear and plastid datasets. The coalescent trees better accommodate disparity in the intron dataset, which contains more parsimony informative sites, while concatenated trees recover more conservative topologies, as they have narrower distribution in the tree landscape. This suggests that highly supported phylogenetic relationships determined in previous studies do not necessarily indicate overwhelming concordant signal. Congruence must be interpreted carefully especially in concatenated datasets. Despite this, the congruence between the multi-species coalescent (MSC) approach and concatenated tree topologies found here is notable. Our analysis does not support Eugenia subg. Pseudeugenia or sect. Pilothecium, as currently circumscribed, suggesting necessary taxonomic reassessment. Five clades are further discussed within Eugenia sect. Umbellatae progress toward its division into workable clades. While targeted sequencing provides a massive quantity of data that improves phylogenetic resolution in Eugenia, uncertainty still remains in Eugenia sect. Umbellatae. The general pattern of higher site coefficient factor (CF) than gene CF in the backbone of Eugenia suggests stochastic error from limited signal. Tree landscapes in combination with concordance factor scores, as implemented here, provide a comprehensive approach that incorporates several phylogenetic hypotheses. We believe the protocols employed here will be of use for future investigations on the evolutionary history of Myrtaceae.